Persistent Fifth Aortic Arch with Coarctation - Kim, Sue Hyun (Korean J Thorac Cardiovasc Surg, 2016)
Persistent fifth aortic arch (PFAA) is a rare congenital anomaly of the aortic arch frequently associated with other cardiovascular anomalies, such as tetralogy of Fallot and aortic arch coarctation or interruption. We report the case of a neonate with PFAA with coarctation who successfully underwent surgical repair.